Meat quality traits and canonical discriminant analysis to identify the use of illicit growth promoters in Charolais bulls. (1st December 2019) - Barbera, S.; Biolatti, B.; Divari, S.; Cannizzo, F.T.
Highlights: Illegal abuse of growth promoters on Charolais bulls identified by meat quality. A portable electronic nose was used to detect the use of illicit growth promoters. The canonical discriminant analysis was useful to identify treated beef. Abstract: The administration of anabolic agents in farm animals to improve meat production has been prohibited in EU, due to the potential risks to human health. Meat quality was investigated to detect the effects of illegal administration of dexamethasone or prednisolone or 17β-estradiol on Charolais bulls. Three groups of 6 bulls were treated and 12 bulls were the control. Meat quality parameters were measured on live animals, carcasses and on samples of Longissimus thoracis and multivariate statistical data analysis was applied. In Charolais bulls, these parameters were affected by growth promoter administration and the multivariate canonical discriminant analysis was able to distinguish between treated and untreated animals mainly due to three electronic nose's parameters, 24 h carcass temperature and drip loss. Therefore, meat quality control and the multivariate analysis could be useful as a first screening to address targeted controls on farms suspected of illicit use of growth promoters.